Looking in the right way: the use of infant observation as a clinical tool in parent−infant psychotherapy with parents with severe mental health difficulties. Issue 2 (3rd May 2016) - Shulman, Graham
Abstract : This article discusses the use and value of infant observation 1 as a clinical tool in parent−infant psychotherapy in the home setting with parents with mental illness or severe and enduring mental health difficulties. A single case study is given of work undertaken in a Child and Adolescent Mental Health Service for parents who are mostly too unwell to attend or access clinic-based services. Parent−infant psychotherapy, like much of the work of this service, is therefore offered in the family home. The home setting makes it a natural context in which to use a psychoanalytic infant observation frame and stance as a clinical tool in psychoanalytic parent−infant psychotherapy. Clinical techniques and methods of psychoanalytic parent−infant psychotherapy are used within an infant observation frame and stance. The article considers some reasons why psychoanalytic infant observation as a clinical tool seems particularly suited and effective with this patient group.